(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
Previous researches show, that social investments in early childhood (until age of 6) are very important, and one of the main types of social investment in this period of time is quality early childhood education and care services (henceforth – ECEC services). Social investments in early childhood have the highest return in human capital, especially for disadvantaged groups of the society. Literature suggests that positive effect of available and qualitative ECEC services can be observed in many areas of life, for example, through improved education indicators, increased participation of the women in the labour market, increased work productivity, higher birth rates, etc. However, the attendance of ECEC services varies considerably between different European Union (henceforth – EU) countries. The aim of this paper is to analyze social investment effect in early childhood in EU countries with high (Denmark), medium (Latvia) and low (Croatia) ECEC service attendance rates, so to find out if and how ECEC service attendance rate in these countries influences such indicators as rate of early leavers from education and training, school graduation rates and female employment rate. To see how situation may change due to the ECEC attendance rate changes in each country analyses was be carried out with imitation model options. This article describes the imitation model, which provides an opportunity to analyze the current situation and compare social investments between different EU countries. The model is designed using ISEE system STELLA MODELING and Imitation Software environment, and it is governed by the criteria that are based on literature studies, as well as analyses of statistic data. An additional benefit is that this model can be adjusted and used to evaluate other countries social investment tendencies as well. Research results show, that not all indicators that have been positively connected with ECEC attendance rate in previous studies have been positively influenced by ECEC attendance rate in chosen case study countries. Analyses showed that only in Croatia positive connections can be observed when it comes to all three indicators. Further studies should be carried out on this topic to get a deeper understanding on ECEC attendance rate effect on these and other indicators, that in the previous studies have been positively linked with ECEC attendance rate.